Identifying Novel Enhancers of the Antitumour Immune Response for Cancer Immunotherapy - Varette, Oliver (Université d'Ottawa / University of Ottawa, 2021)
Immunotherapy is a promising tool in the fight against cancer and aims to recruit patients own immune systems to seek out and destroy malignant cells. Options such as oncolytic viruses (OVs), autologous tumour vaccines and chimeric antigen receptors have shown clinical success to date, yet there remain significant hurdles to overcome. Here, we demonstrate a novel vaccine combining irrCell priming and infected cell boosting dramatically improves the tumour-specific CTL response against CT26 tumours and can be further enhanced using additional immunogenic factors (armed OVs, adjuvants). We also developed a novel fluorescence-based high-throughput screening platform to identify compounds that sensitize resistant solid tumours to killing by CAR-T cells, which ultimately revealed cardiac glycosides as putative tumour sensitizers. Overall, this thesis identifies several novel enhancers of the anticancer immune response, including a heterologous irr:ICV vaccine regimen and the potential ability to identify molecules to overcome resistance to CAR-T therapy.
Keywords: Immunotherapy; Cancer Vaccine; CAR-T Cell; High-throughput screening; Oncolytic Virus; Cancer Immunology